Hibridismos ato-autor e responsabilidade no sistema de justiça juvenil: reflexões desde os escritos de Michel Foucault sobre o direito - Gómez, Alejandra Padilla (2012)
From notions of criminal law by act and criminal law by author, we analysed some theoretical perspectives in the juvenile justice field, using it to articulate the concept of responsibility, which is associated with guilt, in a the legal field and crime theory. Some authors, who support a guarantor perspective, use this notion as a fundamental element to be included in juvenile justice system, which marks the passage from guardianship system to comprehensive integral protection paradigm. Protection system used as the main instrument of "irregular situation" condition, which enables the exercise of a criminal law by author. Integral Protection paradigm is based on the principles of the International Convention on the Rights of Childhood, offering adolescents, who infract, fundamental rights and guarantees which wasn t previously recognized, and according to them, consequently framed to justice under juvenile criminal law by act. In this study, we analysed how, beyond these distinctions, both legal frameworks of juvenile justice and its implementation, are part of a hybrid system, where we can find a coexistence of both models of criminal law by act and criminal law by author. Based on the role of law from Michel Foucault studies, we articulate the conditions of possibility of a criminal law by act with the regime of sovereignty. On the other hand, relate or direct criminal right from disciplinary mechanisms, Correctional Techniques, construction of the criminal, and pathologizing respective normalization techniques. And also, contemporary connotations from the techniques of biopower, which proposes new normalization forms supported by notions of danger and risk. Under these enunciations, we analysed the implication of risk and danger to liability, concluding that in our current political context such notions are articulated in the liability trial. Diagnosing it as dangerous collaborates in risk production strategies and functional mechanisms of biopolitics. We point important reflexions to be taken into account in relation to the subject, particularly in the case of adolescence